Financial Sector Assessment Program : Malawi - Legal Framework for Acceptance, Registration and Realization of Collateral - International Monetary Fund (World Bank, Washington, DC, 2013)
A well-functioning legal framework for secured lending needs to provide for the creation, recognition and enforcement of security interests. This includes making it possible for all types of assets to be collateralized, effective notice and registration rules to be adapted to all types of property, and clear rules of priority on competing claims or interests in the same assets. This working paper includes the following headings: procedure and costs for a secured transaction; registration system; credit reference bureau; realization of collateral; judicial framework; insolvency and corporate rehabilitation; and recommendations.